2019
DOI: 10.20546/ijcmas.2019.806.280
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Content, Uptake, Quality of Chickpea (Cicer arietinum L.) and Fertility Status of Soil as Influenced by Fertilization of Potassium and Sulphur

Abstract: during rabi season of 2014-15 to evaluate soil application of potassium and sulphur on nutrient content, uptake, quality and yield parameter of chickpea (Cicer arietinum L.) under south Saurashtra region of Gujarat. The experiment comprising of four levels of potassium viz., 0, 40, 60 and 80 kg K 2 O ha -1 and sulphur viz., 0, 20, 40, 60 kg S ha -1 and experiment was laid out in Factorial Randomized Block Design and replicated thrice. The results revealed that the content and uptake nutrient, yield of chickpea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This might be due to the fact that sulphur is involve in the formation of chlorophyll and thereby encourages vegetative growth. This result collaborates with the findings of Khatkar et al (2007) [8] , Kaisher et al (2010) [7] and Jadeja et al (2016) [5] . Significantly maximum number of pods/plant (52.47) were observed with the application of 30 kg S/ha (S30) compared to rest of the treatments.…”
Section: Effect Of Sulphursupporting
confidence: 93%
“…This might be due to the fact that sulphur is involve in the formation of chlorophyll and thereby encourages vegetative growth. This result collaborates with the findings of Khatkar et al (2007) [8] , Kaisher et al (2010) [7] and Jadeja et al (2016) [5] . Significantly maximum number of pods/plant (52.47) were observed with the application of 30 kg S/ha (S30) compared to rest of the treatments.…”
Section: Effect Of Sulphursupporting
confidence: 93%
“…The lowest straw yield of chickpea (1825 Kg ha -1 ) was recorded in control treatment T1. Jadeja et al [15], also reported increased Grain and straw yield of chickpea with sulphur application as compared to control. Similar finding of increased stover yield with sulphur application were also given by Srinivasulu et al [11] Fayaz et al [13] and Bhuriya et al [14].…”
Section: Yield Of Chickpeamentioning
confidence: 91%
“…Additionally, Aallamet al (2021) studied the use of Streptomyces species that efficiently solubilize phosphate such as S. bellus and S. enissocaesilis strategies of the acidification of the medium and excretion of siderophores to solubilize phosphate form either organic or inorganic sources. Goud et al (2014) and Jadeja et al (2019) explained that the uptake of potassium and phosphorus by seeds during the growing season is directly related to the application of chemical fertilizers. However, the research of Htweet al, (2019) provides when Streptomyces griseoflavusis co-inoculated with the nodulating forming bacteria Bradyrhizobium japonicum and B. elkaniiin beans and soybean plants, growth parameters, nodulation process and NPK uptake affected positively and have a direct impact on yield production.…”
Section: Chickpeas Seed Evaluationmentioning
confidence: 99%